Arbuscular Mycorrhizal Fungi Contribute to Phosphorous Uptake and Allocation Strategies of Solidago canadensis in a Phosphorous-Deficient Environment - Qi, Shanshan; Wang, Jiahao; Wan, Lingyun; Dai, Zhicong; da Silva Matos, Dalva Maria; Du, Daolin; Egan, Suhelen; Bonser, Stephen P.; Thomas, Torsten; Moles, Angela T. (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) can facilitate the uptake of limiting or inaccessible nutrients by plants. However, the importance of AMF for invasive plants under phosphorus (P) limitation is poorly well understood because of the presence of non-focal microorganisms, such as endophytes or rhizosphere bacteria. In this study, we investigated how an invasive clonal plant Solidago canadensis benefits from the AMF Glomus intraradices by using a completely sterile culturing system, which is composed of aseptic seedlings, a pure AMF strain, and a sterile growth environment. We found that the colonization rate, abundance and spore production of AMF in insoluble P treatment was more than twice as much as insoluble P. Plant above-ground growth was enhanced almost 50% by AMF in insoluble P treatment. Importantly, AMF were able to facilitate P acquisition by the plant in insoluble P conditions, allowing plants to have lower investment into below-ground biomass, and higher benefit/return for above-ground biomass. This study demonstrated the important contribution that AMF make to plants in phosphate-deficient environments eliminating interferences of non-focal microorganisms. Our results also suggest that interaction with AMF could contribute to the invasiveness of clonal plant S. canadensis in resource-deficient environment.